The relations of at-home & out-of-home parental involvement to students’ English language achievement: The influence of educational level and race of parents / Liaw Shun Chone and Angelina Subrayan - Liaw, Shun Chone; Subrayan, Angelina (2008)
This research discussed the strength of relationship between parental involvement and student achievement. Parental involvement in children’s learning at- home and out-of-home is considered crucial to the achievement in the English Language. This study includes both quantitative and qualitative research. The quantitative study consists of a stratified sample of 160 respondents distributed almost proportionally among Malays, Indians and Chinese students. From the same stratified sampling of these ethnic groups, the researchers then used purposive sampling to divide according to families with different levels of parental education. The researchers administered questionnaires to students to investigate 3 research questions, that is, to find out (1) the significant relationship between parental involvement and student achievement (2) the significant difference of levels among Malay, Chinese and Indian students in improving students’ English Language and (3) the significant difference of levels among different PEL groups and student achievement. Spearman correlation r was calculated to determine the relationship strengths between overall parental involvement and student achievement in PMR English Language. Besides the Spearman correlation test, the non-parametric Kruskal Wallis test was used to investigate if there were any significant levels among the three races and PEL groups for at-home and out-of-home parental involvement. Interviews with parents through qualitative research also investigated and determined whether ethnicity and PEL supported quantitative study for at-home and out-of-home parental involvement.